Blood Research - Huh, Hee Jin.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Blood Research is a peer-reviewed open-access journal that delivers significant clinical, translational and basic study results in hematology and related fields to readers worldwide. Blood Research presents coverage on topics from basic laboratory research to clinical studies, translational studies, and precision medicine in the field of hematology. Scope Research articles published in Blood Research cover and include the following categories: Acute Lymphoblastic Leukemia, Adult Acute Lymphoblastic Leukemia, Pediatric Acute Myeloid Leukemia Aplastic Anemia, Immune Thrombocytopenic Purpura Bleeding Disorder, Hemophilia Cell Therapy Chronic Myeloid Leukemia Coagulation Laboratory Histiocytosis Immunology, Infection Laboratory Hematology Lymphoma, CLL Multiple Myeloma Myelodysplastic Syndromes Myeloproliferative Neoplasm, Other Myeloid Malignancy Pediatric Hematologic Malignancy Red Blood Cell Disorder Thrombotic Disorder Transfusion Medicine, Apheresis.
Keywords: Hematology; Oncology; Hematology; Oncology